Synthesis Of Porous TiO2 With Starch Template And Its Photoactivity Towards Photodegradation Of Methylene Blue - Gani Purwiandono; Indriana Kartini (EKSAKTA: Journal of Sciences and Data Analysis, 2015)
Hydrothermal synthesis of TiO2 using starch as pores forming agent has been investigated. The research aimed to investigate the effect of crystallinity and porosity of TiO2 to its photocatalytic activity using photodegradation of methylene blue. TiO2 was synthesized without starch and with various starch concentration (0.5%, 2.5%, 5%, 10% w/v). The starch was dissolved in ethanol,and then was added drop wisely into titanium (IV) tetraisopropoxide(TTIP) solution. The mixture was treated hydrothermally at 100 ºC for 4 h. Starch templatewas removed through calcination at 450 ºC for 4 h. The synthesized TiO2 was characterized by FT-IR spectrophotometry. The effect of starch concentration toTiO2 crystallinity was analyzed using XRD. The porosity of the synthesized TiO2 was determined using N2 gas sorption analyzer. The photocatalytic activity of TiO2 was monitored through the photodegradation of methylene blue. The XRD patterns show that the TiO2 synthesized with various starch concentration consists mainly of anatase crystalline. The particle size of TiO2 synthesized with starch 5% w/v is 11.32 nm with the specific surface area (SBET) of 110.189 m2/g, the total pore volume of 0.2cc/g and the pore diameter of 3.62 nm. The photoactivity test demonstrates that the synthesized TiO2 could degrade methylene blue up to 56.9% under UV irradiation for 30 minutes